2018
DOI: 10.1111/jfbc.12738
|View full text |Cite
|
Sign up to set email alerts
|

Furan-induced cardiotoxicity in diabetic rats and protective role of lycopene

Abstract: The objective of this current study is to search the impacts of furan and lycopene on a diabetic rat's heart. Diabetes increases prevalence with a sedentary lifestyle and obesity. Furan, a carcinogen, was detected in foods that had undergone thermal treatment. Two groups were formed, such as: the control and diabetic groups. Diabetic groups fall into four allocated groups: control, lycopene, furan, and furan + lycopene. The changes in malondialdehide levels, antioxidant enzymes’ activities, and histopathology … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
9
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(10 citation statements)
references
References 46 publications
1
9
0
Order By: Relevance
“…Oxidative stress in the aorta can cause endothelial dysfunction, an initiator and contributing factor to cardiovascular complications of diabetes. 16 Decreased MDA and increased SOD by lycopene treatment, as shown by Zhu et al, are also consistent with many other studies 18,24,25,30,[32][33][34][35][36][37][38][39][40] . A similar study conducted on patients with diabetes showed that lycopene supplementation (4 mg once daily for 3 months) can reduce oxidative stress, as seen from a decrease in MDA and xanthine oxidase levels and an increase in antioxidants such as SOD, GSH, GPx, and GR.…”
Section: Lycopene Ameliorates Oxidative Stress In Dmsupporting
confidence: 89%
“…Oxidative stress in the aorta can cause endothelial dysfunction, an initiator and contributing factor to cardiovascular complications of diabetes. 16 Decreased MDA and increased SOD by lycopene treatment, as shown by Zhu et al, are also consistent with many other studies 18,24,25,30,[32][33][34][35][36][37][38][39][40] . A similar study conducted on patients with diabetes showed that lycopene supplementation (4 mg once daily for 3 months) can reduce oxidative stress, as seen from a decrease in MDA and xanthine oxidase levels and an increase in antioxidants such as SOD, GSH, GPx, and GR.…”
Section: Lycopene Ameliorates Oxidative Stress In Dmsupporting
confidence: 89%
“…Following oral exposure, furan easily permeated through biological membranes, and is rapidly absorbed from the gastrointestinal tract, and metabolized mainly by the liver [9]. Furan was reported to induce injury of many organs and tissues in rodents including; the liver [10], brain [11], kidney [12], and heart [13]. Also, furan was considered by National Toxicology Program (NTP) [14] and International Agency for Research on Cancer (IARC) [15] as "a possibly carcinogenic to humans".…”
Section: Introductionmentioning
confidence: 99%
“…Diabetes mellitus (DM) is a metabolic disorder, defined as abnormally elevated blood glucose, resulting from insufficient insulin secretion or insulin resistance in diabetic patients 1 . Chronic hyperglycaemia in diabetic patients can cause severe damage to various cells and organs, such as the retina, heart, kidney, and blood vessels 2 . Recent studies have demonstrated that the prevalence of diabetes mellitus has increased from 451 million people in 2017 and is estimated to reach 693 million by 2045 3 .…”
Section: Introductionmentioning
confidence: 99%
“…Most of the patients (more than 90%) with elevated blood glucose levels are diagnosed with type 2 DM (T2DM), which is pathologically insulin‐independent 4 . T2DM is characterized by the resistance of hepatocytes, adipocytes, and myocytes to insulin, resulting in progressive cell dysfunction and hyperglycaemia 2 . Previous studies have shown that hyperglycaemia increases the production of free radicals, and oxidative stress 5,6 …”
Section: Introductionmentioning
confidence: 99%